2008
DOI: 10.1002/jcb.21769
|View full text |Cite
|
Sign up to set email alerts
|

A novel butyrolactone derivative inhibited smooth muscle cell migration and proliferation and maintained endothelial cell functions through selectively affecting Na, K‐ATPase activity and mitochondria membrane potential during in vitro angiogenesis

Abstract: We have found that 3-benzyl-5-((2-nitrophenoxy) methyl)-dihydrofuran -2(3H)-one (3BDO), could effectively suppress human umbilical vascular endothelial cell (HUVEC) apoptosis induced by deprivation of fibroblast growth factor-2 and serum. Here, our purpose was to investigate whether 3BDO could modulate angiogenesis and its possible acting mechanism. The effect of 3BDO on angiogenesis was investigated by capillary-like tubule formation and rat aortic ring assay. Proliferation and migration of cells were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Na + -K + -ATPase and Ca 2+ -ATPase were measured as previously described [16, 36]. The inorganic phosphate–molybdate complex was quantitated by spectrophotometer at 690 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na + -K + -ATPase and Ca 2+ -ATPase were measured as previously described [16, 36]. The inorganic phosphate–molybdate complex was quantitated by spectrophotometer at 690 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In mitochondrial preparations, N-acetylcysteine (NAC), glutathione, and vitamin C prevent ROS production caused by high concentrations of Mn [16]. In cultured astrocytes, Chen and Liao [17] observe that NAC attenuates the pro-oxidant effects of Mn.…”
Section: Introductionmentioning
confidence: 99%
“…SFO, even in the presence of serum and FGF‐2, can inhibit endothelial angiogenesis through inducing apoptosis (Zhao et al, 2006). In contrast, 3BDO, which inhibits apoptosis of HUVECs, facilitates endothelial migration and tubule formation through inhibiting Na, K‐ATPase activity (Meng et al, 2008). In addition, chloroquine (CQ) can induce HUVEC vacuolation and accumulation of microtubule‐associated protein 1 light chain 3‐II (MAP1 LC3‐II), a specific marker for autophagy.…”
Section: Integrin β4 In Endothelial Angiogenesismentioning
confidence: 99%
“…Further study indicated that 3BDO selectively protected vascular ECs (VECs) and inhibited vascular smooth muscle cell (VSMC) proliferation and migration18. Moreover, 3BDO could inhibit the injury induced by chloroquine and lipopolysaccharide in HUVECs1920.…”
mentioning
confidence: 98%